1998
DOI: 10.1007/s004390050806
|View full text |Cite
|
Sign up to set email alerts
|

The Usher syndrome in the Lebanese population and further refinement of the USH2A candidate region

Abstract: Usher syndrome (USH) is an autosomal-recessive disease characterized by neurosensory deafness and progressive retinitis pigmentosa. So far, three clinical types of Usher syndrome have been defined, and are caused by defects at more than eight loci. We report the linkage analysis of seven Lebanese families with Usher syndrome, two with type I (USH1) and five with type II (USH2). We demonstrate that one family is linked to the USH1C locus, a rare form of USH1 only reported in the French Acadian population. Linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
(45 reference statements)
0
17
2
Order By: Relevance
“…Ocular examinations included measurement of visual acuity, funduscopy, visual field examination, color vision testing, and retinoscopy. Blood samples were taken from all members of this family, USHLB3, 12 and DNA was extracted according to standard methods.…”
Section: Ophthalmic Geneticsmentioning
confidence: 99%
“…Ocular examinations included measurement of visual acuity, funduscopy, visual field examination, color vision testing, and retinoscopy. Blood samples were taken from all members of this family, USHLB3, 12 and DNA was extracted according to standard methods.…”
Section: Ophthalmic Geneticsmentioning
confidence: 99%
“…The chromosome 1q41 region containing USH2A was narrowed to 2.1 cM by Kimberling et al [1995], a YAC contig was constructed , and the region was further refined [Bessant et al, 1998;Saouda et al, 1998]. After construction of a BAC contig, Eudy et al [1998] identified the USH2A gene by detection of mutations in a patient's DNA.…”
Section: Ush2amentioning
confidence: 99%
“…2), has been identified as a gene whose mutation causes the disease. Here, we report a gene underlying USH1C (MIM 276904), a USH1 subtype described in a population of Acadian descendants from Louisiana 3 and in a Lebanese family 4 . We identified this gene (USH1C), encoding a PDZ-domain-containing protein, harmonin, in a subtracted mouse cDNA library derived from inner ear sensory areas.…”
mentioning
confidence: 99%
“…The 180-bp PCR fragment encompassing the intron 5/exon 6 junction was digested with BstUI, which recognizes the CGCG mutated sequence. The parents (1,2) are heterozygous for the mutation, the three affected children (3,4,5) are homozygous. In agreement with the reported haplotypes 4 , three (7,8,9) of five unaffected children are carriers and two (6, 10) are non-carriers.…”
mentioning
confidence: 99%